2014
DOI: 10.1155/2014/201482
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Synergistic Action of Differentially Synthesized Silver Nanoparticles with β-Cephem Antibiotics and Chloramphenicol

Abstract: Synergistic activity of cephem antibiotics with silver nanoparticles (Ag NPs) was investigated. Silver nanoparticles were synthesized through biological and chemical method. The combined action of -lactam cephem antibiotics with both green and chemically synthesized silver nanoparticles enhances the antibacterial activity against wide range of antibiotic resistant pathogens and making them applicable to medical devices and microbial control systems. Synergistic activity of chloramphenicol with silver nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…In their report, AgNPs were recommended with and without antibiotics for controlling the pathogens. 23 Taking together, our results confirmed that synergistic effects of antibiotics combined with AgNPs cannot be considered as a rule. Since AgNPs may have different shapes and sizes, and be modified with different coatings, this may lead to differences in their effects in combination with different antibiotics.…”
Section: Discussionsupporting
confidence: 70%
“…In their report, AgNPs were recommended with and without antibiotics for controlling the pathogens. 23 Taking together, our results confirmed that synergistic effects of antibiotics combined with AgNPs cannot be considered as a rule. Since AgNPs may have different shapes and sizes, and be modified with different coatings, this may lead to differences in their effects in combination with different antibiotics.…”
Section: Discussionsupporting
confidence: 70%
“…This is particularly important in view of the increasing epidemic of drug-resistant pathogens, as several bacteria have developed resistance against conventional antibiotics. It is also notable that biologically synthesized AgNPs have previously shown better synergistic effects as compared to chemically derived AgNPs (Hari et al, 2014). This is attributable to the differential capping of biogenic and chemically synthesized nanoparticles, and is consistent with reports of the direct impact of silver nanomaterial capping on antibiotic sensitive and resistant strains of bacteria (Tiwari et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…13a, b, it can be confirmed that combining the antibiotics with AgNPs resulted in a greater bactericidal effect on test pathogens than either of the antibacterial agents used alone. Inhibition of Escherichia coli might have been facilitated by silver's high affinity for phosphorus and sulphur which are part of the cell membranes of Gram-negative bacteria [38]. The sulphur and phosphorus reacts with AgNPs causing dysfunction of enzymes on bacteria cell wall and also it disturbs DNA's moieties process thereby denying replication [39].…”
Section: Evaluation Of Antibacterial Activity Of Synthesized Silver Nmentioning
confidence: 99%